The valid generic names for the fish species usually placed in Cyclocheilichthys (Pisces: Cyprinidae) - Kottelat, Maurice (Zootaxa, 2013)
Cyclocheilichthys is the valid name for the genus that includes Barbus apogon Valenciennes. Cyclocheilichthys has precedence over Anematichthys, which is a simultaneous objective synonym. If C. enoplos is considered not to be congeneric with C. apogon, the valid name for a genus that includes it is Cyclocheilos.